Levan based bıodegradable hydrogels for drug delıvery - Osman, Asıla (My University, 2016)
İlaç Taşınımında Kullanılacak Levan Bazlı Biyobozunur Hidrojeller Son yıllarda kontrollü ilaç taşıyıcı sistemlere artan bir şekilde ilgi duyulmaktadır. Kontrollü ilaç taşıyıcı sistemler kullanılarak önceden belirlenen süreler içierisinde ilacın salımı mümkün olabilmektedir. Bu amaç için akıllı ilaç taşıyıcı sistemler kullanılmaktadır. Sıcaklık duyarlı polimerler içinde en fazla ilgi çeken polimer poli (N-izopropil akrilamid), pNIPA dır. PNIPA her ne kadar vücut sıcaklığına yakın hacım-faz değişimi sıcaklığına (VPTT) sahip olduğu için kontrollü ilaç salım çalışmlarında önemli bir potansiyele sahip olsa da, biyo-uyumlu olmaması nedeniyle enflamasyona sebep olabilmektedir. Öte yandan pNIPA esaslı hidrojellerin hazırlanmasında çapraz bağlayıcı olarak kullanılan N-metilen-bis-akrilamid (BAAM) da biyo-uyumu olmayıp toksiktir. Bu nedenlerden dolayı PNIPA esaslı hidrojellerin hazırlanmasında hem biyo-uyumluluğu arttırmak, hem de çapraz bağlayıcı olarak kullanmak için biyo-uyumlu polimerlerden hazırlanan çapraz bağlayıcılar sentezlenmektedir. Bu çalışmada, biyo-uyumlu çapraz baplayıcı olarak metakrillenmiş levan (MA-levan) sentezlendi. Sentezlenen metakrillenmiş levan çapraz bağlayıcıolarak kullanularak, 5-amino salisilikasitin kontrollü ilaç salımında kullanılmak üzere, levan-pNIPA esaslı hidrojeller değişik levan/ pNIPA oranlarında redox polimerizasyonu tekniği ile, potasyum persulfat ve TEMED başlatıcı olarak kullanılarak oda sıcaklığında sentezlendi. Sentezlenen levan esaslı biyouyumlu ve biyo-bozunur çapraz bağlayıcı Fourrier transform infrared spktroskopi (FT-IR), 1H-nükleer manyetik rezonans spektroskopisi (1H-NMR), jel geçirgenliği kromatografisi-ışık saçılması (GPC-LS), diferansiyel tarmalı kalorimetre (DSC) ve termal graivmetrik analiz (TGA) tehnikleri ile analiz edildi. Sentezlenen MA-levanın çapraz bağlayıcı olarak kullanıldığı farklı levan/ pNIPA oranlarındaki hidrojeller sentezlenerek bunların 25 oC, 30 oC, 35 oC, 40 oC sıcaklıklarda fosfat tampon (PBS, pH=7.4) içindeki şişme davranışları incelendi. Sentezlenen hidrojellerin VPTT sıcaklıkları türevsel diferansiyel taramalı kalorimetre (DDSC) ile hasas olarak tayin edildi. Hidrojellerin VPTT sıcaklıklarının artan pNIPA oranıyla 32.8 oC tan (saf pNIPA) 35.09 oC ye (Gel-1, %60 pNIPA, %40 levan içermektedir) arttığı gözlendi. Hidrojellerden 5-ASA salımı UV-VIS spektroskopisi ile izlendi. Hidrojellerin şişme ve 5-ASA salım davranışlarının sıcaklık ve kompozisyon ile önemli oanda değiştiği gözlendi. Hidrojellerin biyo-uyumlulukları fare fibroblast L929 hücre hattına karşı belirlendi. Artan levan oranıyla birlikte hidrojellerin biyo-uyumluluklarında da artış gözlendi. Levan, N-izopropil akrilamid, 5-ASA, sıcakl duyarlı hidrojel, kontrollü salım, ilaç taşıma and biyo-polimerler

LEVAN BASED BIODEGRADABLE HYDROGELS FOR DRUG DELIVERY The need for controlling the release of drug has increased in the past decades. Delivery of compounds occurs in predetermined period of time while controlling the amount of drug with respect to time. For this purpose, the new trend is the use of smart hydrogel as a drug delivery system. One of the well-known temperature responsive polymers is poly (N-isopropyl acrylamide), pNIPA. Although, pNIPA hydrogels have a great potential for smart drug delivery systems since they have a volume phase transition temperature (VPTT) close to body temperature, they are not bio-compatible and thus may cause possible inflammation on use. In addition, non-biocompatible cross-linker, N-methylene bis-acrylamide (BAAM) is mostly used as cross-linker in the preparation of pNIPA hydrogels. To eliminate BAAM and to increase the biocompatibility, specific cross-linkers prepared from biodegradable polymers have been used. In this study, methacrylated levan (MA-levan) was synthesized as biodegradable cross-linker. Using MA-levan, for 5-aminosalyciylic acid (5-ASA) delivery, biocompatible and temperature sensitive levan/ N-isopropyl acrylamide (levan/ PNIPA) hydrogels have been successfully synthesized by redox polymerization using potassium peroxodisulfate and TMED as redox pairs at room temperature. Characterization of the synthesized biodegradable cross-linker was successfully performed by using Fourrier transform infrared spectroscopy (FTIR), 1H nuclear magnetic resonance spectroscopy (1H-NMR), gel permeation chromatography-light scattering (GPC-LS), differential scanning calorimetry (DSC) and thermal gravimetric analysis (TGA). Different biodegradable hydrogels at varying levan/ PNIPA ratios were prepared and their swelling behaviors have been investigated in PBS (pH=7.4) at four different temperatures namely 25 oC, 30 oC, 35 oC, 40 oC. Volume phase transition temperatures (VPTT) of the hydrogels were sensitively determined by derivative differential scanning calorimetry (DDSC). It was noticed that phase transition temperatures were increased from 32.8 oC (for pure PNIPA) to 35.09 oC (for Gel-4 which contains 40% levan, 60% pNIPA) with increasing levan ratio. Moreover, the thermal stability has been investigated using TGA. A remarkable increase in thermal stability of levan within hydrogel with increase of pNIPA content was recorded. The release of 5-ASA from the hydrogels was followed by UV–Vis and fluorescence spectroscopy. Swelling behaviors and the release of 5-ASA varied significantly with temperature and the gel composition. The biocompatibility of the hydrogels was tested against mouse fibroblast L929 cell line in PBS. The hydrogels showed increasing bio-compatibility with increasing levan ratio indicating levan enhanced the hydrogel surface during swelling. Key words: Levan, N-isopropyl acrylamide, 5-ASA, temperature sensitive hydrogel, controlled release, drug delivery and biopolymers.
Keywords: İlaç taşıma sistemleri; Kimya, Mühendislik